Imunodeficiência primária por défice de ZAP-70 - Barata, LT (2001)
The authors present the case of a child with recurrent infections since the age of 4 months, including bilateral pneumonia by Pneumocystis carinii and protracted varicella. Serum immunoglobulin values (when 10 months old), and B cell values were normal. There was persistent lymphocytic leucocytosis, near absence of CD8+ cells, and an increased CD4/CD8 ratio. The percentage of activated T cells and the expression of HLA class I were normal. Proliferation, activation and IL-2 synthesis studies in T cells showed a TCR/CD3-associated signal transduction deficit. ZAP-70 cDNA sequencing showed a mutation, and no ZAP-70 protein was detected in T cells. ZAP-70 deficiency is associated with a rare immune deficiency with absence of CD8+ T cells as well as a functional deficiency in T cells. Seven months after bone marrow transplantation the child is clinically well and immunologically recovered